Comparison of geotechnical properties of laterite, kaolin and peat - Mohd Yusoff, S. A. N. (2014)
Geotechnical properties are influenced by the different types of soil. The objective of this study was to investigate the behaviour of geotechnical properties on different types of soil. This paper compares some geotechnical properties of Kaolin, Laterite and Peat. Laterite was collected from Bukit Banang while Peat sample was collected from Parit Nipah, both locations were in Batu Pahat, Johor. Meanwhile, kaolin that was used in this research was manufactured kaolin. A laboratory testing program consists of basic properties tests were conducted in order to obtain general information on the materials (e.g Natural moisture content, Atterberg Limit, Specific gravity, grain size analysis, chemical composition and pH). Further tests have been carried out in determining the geotechnical properties of the soil which evaluates its behaviour for design and construction suitability. The results showed that the Natural/initial moisture content for, peat is higher than laterite and kaolin. Meanwhile Specific gravity for Peat is the lowest among kaolin and laterite. It was also found that the pH of all soil is acidic which lay in the range of 3.76-5.95.The UCS and CBR is compacted in same energy and been tested. This paper summarizes the result of analysis performed on all tests conducted. From the study it can be summarized that geotechnical properties of a soil is highly depending on its type